Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Masyarakat Dalam Membayar Pajak di Kota Pekalongan - Hadi, M Hadi Asfari; Khoiri Furqon, Imahda (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2025)
This study aims to analyze the factors that influence the compliance of the people of Pekalongan City in paying taxes. Using a qualitative descriptive approach, data were obtained through interviews, observations, and literature studies. The results of the study indicate that low public compliance is influenced by four main factors: low taxpayer awareness, lack of knowledge about taxation, negative attitudes towards the government, and ineffective tax socialization. Low taxpayer awareness is caused by a lack of understanding of the benefits of taxes for development. Public knowledge about tax procedures and mechanisms is also limited, causing confusion. In addition, negative perceptions of government transparency in tax use worsen taxpayer motivation. The socialization carried out often does not reach all levels of society, especially those who have limited time or access. To overcome this obstacle, the study recommends more intensive and inclusive tax education, simplification of procedures, improvement of the quality of public services, and strict law enforcement. These efforts are expected to increase taxpayer awareness and compliance, support sustainable development, and create a better tax compliance culture in Pekalongan.Keywords: tax compliance, public awareness, tax socialization, Pekalongan City, public service